George Santayana’s Teleological Poetics: Inspiration, Knowledge and Happiness in Reason in Art (Castilla. Estudios de Literatura, 2012)
With The Life of Reason George Santayana earned his reputation as philosopher; this is due to its length but also because it is his most detailed moral work. The fourth volume of the work, entitled Reason in Art, analyzes both the historical and synchronic origin of the work of art. Santayana’s Poetics are built on the strained relationship he draws between, ethics and aesthetics, ingenium and ars, literature and philosophy. He develops a teleological and eudaimonistic approach which centres on three concrete loci: inspiration, knowledge and happiness.